2022
DOI: 10.1029/2021ja029867
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Magnetic Flux Ropes in the Nightside Induced Magnetosphere of Mars and Venus

Abstract: Magnetic flux ropes are characteristic helical twisted magnetic field structures, widely considered to form as consequences of magnetic reconnection or plasma instability. A typical flux rope has a strong magnetic field along its central axis and a weaker and purely twisted magnetic field at its boundary (e.g., Eastwood & Kiehas, 2015). Flux ropes (sometimes being called plasmoids, magnetic clouds, and flux transfer events) have been observed throughout our solar system, including Earth magnetosphere (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
1
2
1
Order By: Relevance
“…In addition, we have to remind the readers that our results reveal the average morphology of the tail current sheet. Given the large variability of the cross-tail current sheet location in MSE coordinates (e.g., twisted effect), the averaged characteristics of individual tail current sheets might be different to our results (e.g., DiBraccio et al, 2018;Hara et al, 2022;Harada et al, 2017).…”
Section: Average Structure Of the Magnetotail Current Sheetcontrasting
confidence: 87%
See 1 more Smart Citation
“…In addition, we have to remind the readers that our results reveal the average morphology of the tail current sheet. Given the large variability of the cross-tail current sheet location in MSE coordinates (e.g., twisted effect), the averaged characteristics of individual tail current sheets might be different to our results (e.g., DiBraccio et al, 2018;Hara et al, 2022;Harada et al, 2017).…”
Section: Average Structure Of the Magnetotail Current Sheetcontrasting
confidence: 87%
“…Recent studies have demonstrated that the crustal fields could complicate the structure of Martian magnetotail (DiBraccio et al, 2018(DiBraccio et al, , 2022Hara et al, 2022;Luhmann et al, 2015;Xu et al, 2020). The open field lines generated by the reconnection between IMF and crustal fields will overlap with the induced field lines, leading to the twist tail.…”
Section: Discussionmentioning
confidence: 99%
“…The quasi-perpendicularity between the axis and M CS , as well as the opposite helicities of the flux ropes on either side of the current sheet, suggest they may be generated by dayside ionospheric instabilities and dragged into the tail by the solar wind. The criterion and result are consistent with previous research (e.g., Hara et al, 2022Hara et al, , 2017bLuhmann & Cravens, 1991).…”
Section: Flux Ropes On the Edge Of The Current Sheetsupporting
confidence: 92%
“…The magnetic observation signature of a flux rope is susceptible to its orientation, as well as the spacecraft trajectory through the flux rope. The LMN coordinates obtained from the minimum variance analysis (MVA) (Sonnerup & Scheible, 1998) has been proven to be advantageous in determining the orientation and structure (e.g., Bowers et al., 2021; Briggs et al., 2011; Hara et al., 2022; Sibeck et al., 1984; Vignes et al., 2004). The L, M, and N represent the maximum, intermediate, and minimum variance direction, and their corresponding eigenvalues are λ L , λ M, and λ N , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Sinuous aurora also depends strongly on IMF clock angle, with occurrence twice as likely for northnortheast and south-southwest clock angles. Sinuous aurora orientation shows a complex dependence on clock angle whereby sinuous aurora are approximately aligned with the solar wind convection electric field (E conv ) direction, albeit with significant scatter and moderate counterclockwise and clockwise twists in MSE coordinates for eastward and westward IMF conditions, respectively, similar to twists observed in the magnetotail current sheet by Hara et al (2022). Lastly, sinuous aurora appear almost exclusively in the hemisphere to which E conv points.…”
Section: Discussionmentioning
confidence: 82%